Efforts of the British Empire to Build a State in Iraq After the First World War - İsmail Şahin; Cemile Şahin; Samet Yüce (Gazi Akademik Bakış)
This study searches for the policies carried out by the British Empire in Mesopotamia where the British invaded during the First World War. However, it will be convenient to know the political, social and economic background of Iraq or Mesopotamia as a general outline to understand the period clearly. Therefore, we have primarily tried to explain the overview of pre-invasion in Iraq. The traditional social structure of the Iraqi population and their relationship with the administration and each other have been questioned in the context of national identity. Then the developments in Iraq after the invasion have been discussed.The strategies which the Britain used to rule Iraq and the public’s reaction to this strategy have been investigated. In this context, the facts and the events such as the Mandate, 1920 Arab Revolt, the Cairo Conference of 1921 and the Kingdom of Iraq have been focused. It has been endeavored to per-form an analysis to understand the present problems in Iraq by discussing the cause and effect relations of the facts and the events. The research has been prepared by benefiting from a rich bibliography based on the scientific works of the experts for Iraq and the Middle East. As a result, this research has revealed the difficulties in ruling Iraq both internally and externally due to its sui generis political, social and economic conditions and found out that the mistakes made in the nation building process have caused the instability occured at the present time in the country.